Highly Safe, Durable, Adaptable, and Flexible Fuel Cell Using Gel/Sponge Composite Material (Adv. Energy Mater. 6/2022). Issue 6 (10th February 2022) - Zou, Siyi; Li, Yali; Jin, Hanqing; Ning, Fandi; Xu, Pengpeng; Wen, Qinglin; Pan, Saifei; Dan, Xiong; Li, Wei; Zhou, Xiaochun
Abstract : Fuel Cells In article number 2103178, Xiaochun Zhou and co‐workers prepare a highly safe, durable, adaptable, and flexible air‐breathing direct methanol fuel cell by synthesizing and applying a new composite material with agar gel and wood sponge, that is, a gel/sponge composite.